Instruments evaluating the self-directed learning abilities among nursing students and nurses: a systematic review of psychometric properties. Issue 1 (December 2017) - Cadorin, Lucia; Bressan, Valentina; Palese, Alvisa
Abstract Background Modern healthcare institutions are continuously changing, and Self-Directed Learning (SDL) abilities are considered a prerequisite for both nursing students and nurses in order to be proactive about these demanding challenges. To date, no systematic reviews of existing instruments aimed at detecting and critically evaluating SDL abilities have been published. Therefore, the aims of this review are: 1) identify the instruments for assessment of SDL abilities among nursing students and nurses; 2) critically evaluate the methodological studies quality; and 3) compare the psychometric properties of the available instruments. Methods A psychometric-systematic-review was performed. CDSR, CINAHL, ERIC, MEDLINE, PROSPERO, SCOPUS databases were searched without restrictions in time and setting. All primary studies involving nursing students or nurses, written in English and aimed at validating SDL assessment tools, were included. Studies retrieved were evaluated according to the COnsensus-based-Standards for the selection of health Measurement-INstruments (COSMIN) panel. Study inclusion, data extraction and quality assessment were performed by researchers independently. Results Eleven studies were included and four tools based on Knowles's theory have emerged: 1) the Self-Directed Learning Readiness Scale; 2) the Self-Directed Learning Readiness Scale for Nursing Education; 3) the Self-Rating Scale of Self-Directed Learning, and 4) the Self-Directed Learning Instrument. A few psychometric properties have been considered in each study, from two to four out of the ten required. The quality of the methodologies used was in general, from fair to poor with the exception of one instrument (the Self-Directed-Learning-Instrument). The psychometric proprieties that emerged across the tools were good in general: the Cronbach α was from 0.73 to 0.91; structural validities have also reported good indexes both in the explorative and in the confirmative factor analyses. Conclusions On the basis of the findings, the Self-Directed-Learning-Instrument can be recommended for the assessment of SDL abilities among nursing students and nurses, given the excellent methodology quality adopted in estimating the psychometric properties. However, rigorous study designs aimed at estimating psychometric properties of tools in wide samples of nursing students and nurses across different stages of professional life, from undergraduate education to professional maturity, in different cultural, educational, and work settings, are strongly recommended.